A pair-wise approach to testing for output and growth convergence - Mohammad Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper proposes a pair-wise approach to testing for output convergence that considers all N(N-1)/2 possible pairs of log per capita output gaps across N economies. A general probabilistic definition of output convergence is also proposed, which suggests that all such output gap pairs must be stationary with a constant mean. The approach is compatible with individual output series having unit roots, does not involve the choice of a reference country in computation of output gaps, and can be applied when N is large relative to T (the time dimension of the panel). The proposed test is applied to output series in the Penn World Tables over 1950-2000, as well as to Maddion's historical series over 1870-2000. Overall, the results do not support output convergence, and suggest that the findings of convergence clubs in the literature might be spurious. However, significant evidence of growth convergence is found, a result which is reasonably robust to the choice of the sample period and country groupings. Non-convergence of log per capita outputs combined with growth convergence suggests that while common technological progress seems to have been diffusing reasonably widely across economies, there are nevertheless important country-specific factors (for example, wars, famines, revolutions, regime and institutional changes) that render output gaps highly persistent, such that we can not be sure that the probability for the output gaps to lie within a fixed range will be non-zero.
Keywords: C32; C33; D90; O47; 330; economic growth; panel data models; common technological shocks; convergence; Entwicklungskonvergenz; Sozialprodukt; Panel; Vergleich; Welt